Zero-bias mid-infrared graphene photodetectors with bulk photoresponse and calibration-free polarization detection - Jingxuan Wei (Nature Portfolio, 2020)
Here, graphene-based plasmonic metamaterials are used to generate an artificial bulk photovoltaic effect, enabling the realization of mid-infrared photodetectors with enhanced responsivity and calibration-free polarization detection at room temperature.